PERFORMANCE ACCOUNTABILITY SYSTEM DEVELOPMENT IN ONLINE-BASED GOVERNMENT INSTITUTION - Kezia Arum Sary; Abdullah Karim; Bambang Irawan; Najahatul Hananah (Jurnal Ekonomi dan Manajemen, 2021)
In this case the Samarinda City Government plans to implement a system to monitor and evaluate the performance of government agencies. The system will be implemented in all SKPD in Samarinda City. In order to accelerate Bureaucratic Reform in Government Agency Performance Accountability by utilizing information and communication technology, it is needed today. This effort is a quick and precise step in synching accurate performance data and databases. In this application a joint commitment is required by maximizing available resources such as HR, hardware/internet networks. In connection with this, the Samarinda City Government has developed an online-based agency performance accountability system called G-SAKIP that is very simple in the hope of facilitating planning to performance reporting. In this G-SAKIP Application a very important preliminary document prepared by SKPD is the Strategic Plan (RENSTRA).